2015
DOI: 10.1586/14737175.2015.1058161
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of speech and language therapy for aphasia after stroke: more evidence needed

Abstract: Aphasia due to stroke affects communication and quality of life. Most stroke survivors with aphasia receive speech and language therapy. Although an early start of treatment is advocated in clinical practice, evidence for "The earlier, the better" in aphasia rehabilitation is weak. Hence, clinicians are faced with the dilemma of when to initiate intensive treatment: as early as possible, when most of the spontaneous recovery occurs but when patients are often ill, or later, when the patients' condition is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 69 publications
0
16
0
3
Order By: Relevance
“…Although several studies point to a larger effect of aphasia therapy if applied in the first 3 months after stroke, (Robey, 1998; Bakheit et al, 2007a) a recent review showed that the currently available evidence on the optimal timing of aphasia therapy is inconclusive and insufficient (Nouwens et al, 2015). The contradictory findings may be related to differences in study populations, e.g., including persons with various types of aphasia and/or receiving different types of aphasia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies point to a larger effect of aphasia therapy if applied in the first 3 months after stroke, (Robey, 1998; Bakheit et al, 2007a) a recent review showed that the currently available evidence on the optimal timing of aphasia therapy is inconclusive and insufficient (Nouwens et al, 2015). The contradictory findings may be related to differences in study populations, e.g., including persons with various types of aphasia and/or receiving different types of aphasia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the trial also revealed an improvement in communicative quality of life (Cohen's d=0. 27), an important finding that had eluded many earlier trials (e.g., references [23][24][25] ). Taken together, large meta-analyses and the Breitenstein et al 18 trial provide robust evidence in favor of SLT for post-stroke aphasia.…”
Section: Efficacy Of Behavioral Speech and Language Therapy For Aphasiamentioning
confidence: 95%
“…the interval between stroke onset and start of treatment, and its efficacy is unclear. 4 In a meta-analysis comparing studies with different starting points of SLT, the average effect size in studies evaluating treatment initiated in the first 3 months after stroke was larger than that in studies performed in a later stage. 5 However, this analysis was mainly based on uncontrolled and non-randomised studies.…”
Section: Introductionmentioning
confidence: 96%